2018
DOI: 10.4103/ipj.ipj_95_14
|View full text |Cite
|
Sign up to set email alerts
|

The sociocultural factors and patterns of help-seeking among patients with mental illness in the sub-Himalayan region

Abstract: Context: Selection of first help in psychiatric illnesses depends on various sociodemographic and environmental factors. In integrated societies like India careers also contribute in deciding help-seeking behavior of psychiatric patients. In this study, we explored these factors and the role of education of decision maker, i.e., person who is final authority in deciding the course of management. Aims: This study aims to study sociocultural factors and patterns of help-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…where they found that easy accessibility followed by trust in faith healers are good reasons to access the faith healers. [ 25 ] In a study by Pal SK et al . regarding various types of treatment strategies adopted by families of patients with epilepsy in north western India found that families did adopt some culturally prevalent methods to control involuntary movements during seizures.…”
Section: Discussionmentioning
confidence: 99%
“…where they found that easy accessibility followed by trust in faith healers are good reasons to access the faith healers. [ 25 ] In a study by Pal SK et al . regarding various types of treatment strategies adopted by families of patients with epilepsy in north western India found that families did adopt some culturally prevalent methods to control involuntary movements during seizures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, support from family and well-wishers proved beneficial in sustaining engagement with professional help-seeking [53]. Education of the decision-maker significantly influenced help-seeking behaviors [54]. Patients and caregivers having higher awareness about mental illness sought help from mental health professionals sooner, whereas, those with lower awareness contacted faith healers first [49].…”
Section: Studies On Treatment-seeking Samplesmentioning
confidence: 99%
“…This finding resembles the observation in an Indian study which found no significant association of ICD-10 diagnostic groups with seeking care from faith healer or psychiatrist. 14 The most common reasons for visiting faith healers in the present study were cultural perception of mental disorders and belief in miraculous cure. This is almost similar to the observations made by earlier studies which have talked about cultural/religious beliefs and magical cure beliefs as reasons for faith healer visits.…”
Section: Discussionmentioning
confidence: 66%
“…An earlier Indian study had noted no significant association of marital status with faith healer visit. 14 An earlier study from Kerala also showed a similar distribution of religions and showed no preponderance among any religion to visit faith healers. 11 There was no association of psychiatric diagnosis with seeking faith healers.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation